Functional anatomy of the lymphatics draining the skin: a detailed statistical analysis - Reynolds, Hayley M (Blackwell Science Inc, 2010)
Relatively little is known about the functional anatomy of the lymphatic vessels draining the skin. To address this issue, we previously created a three-dimensional computer model of skin lymphatic drainage, using melanoma lymphoscintigraphy (LS) data from 5232 patients. In this study we sought to extend our model by performing a detailed statistical analysis of the mapped LS data to characterize the functional anatomy of the superficial lymphatics without any a-priori spatial bias. We investigated the commonly held assumption that lymphatic drainage is symmetric between the two sides of the body. Results indicated that, with the exception of the lower anterior torso, posterior leg and a small section of the posterior torso, most skin regions with sufficient data showed symmetric drainage. LS data from each symmetric skin region were then reflected to the opposite side of the body to provide an increased LS dataset for subsequent analysis. Cluster analysis was then applied to this reflected LS dataset to group regions of skin that drained in a similar manner. Results defined nine large clusters of skin, largely draining to the dominant axillary, groin, cervical level II and preauricular node fields. Each of the four axillary and groin node fields defined large clusters of skin on the torso, dividing it into regions similar to the historical ‘Sappey's lines’, although a fifth region of highly ambiguous drainage was also shown in the anterior and posterior center of the torso. Collectively, these results provide important new insights into skin lymphatic drainage, both improving and quantifying our understanding of functional lymphatic anatomy.